A human periodontal ligament fibroblast cell line as a new model to study periodontal stress - Weider, Matthias; Schröder, Agnes; Docheva, Denitsa; Rodrian, Gabriele; Enderle, Isabel; Seidel, Corinna Lesley; Andreev, Darja; Wegner, Michael; Bozec, Aline; Deschner, James; Kirschneck, Christian; Proff, Peter; et al. (International Journal of Molecular Sciences, 2020)
The periodontal ligament (PDL) is exposed to different kinds of mechanical stresses such as bite force or orthodontic tooth movement. A simple and efficient model to study molecular responses to mechanical stress is the application of compressive force onto primary human periodontal ligament fibroblasts via glass disks. Yet, this model suffers from the need for primary cells from human donors which have a limited proliferative capacity. Here we show that an immortalized cell line, PDL-hTERT, derived from primary human periodontal ligament fibroblasts exhibits characteristic responses to glass disk-mediated compressive force resembling those of primary cells. These responses include induction and secretion of pro-inflammatory markers, changes in expression of extracellular matrix-reorganizing genes and induction of genes related to angiogenesis, osteoblastogenesis and osteoclastogenesis. The fact that PDL-hTERT cells can easily be transfected broadens their usefulness, as molecular gain- and loss-of-function studies become feasible.
CRIS-Team Scopus Importer:2020-11-13
Keywords: Bone remodeling; Cell culture techniques; Mechanical loading; Orthodontic tooth movement